Design of Hydroelectric Power Plant Demonstration Tools for Mentality Retarded Students - Is, Fashbir; Hari Anna Lastya (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
Children with disabilities often have difficulty understanding abstract concepts, requiring concrete and visually accessible learning media. The purpose of this study was to design and evaluate the feasibility of a Hydroelectric Power Plant (PLTA) demonstration tool as a science learning tool for children with intellectual disabilities. This study used a Research and Development (R&D) approach based on the Borg and Gall model. The developed PLTA demonstration tool uses simple and safe components, such as a water pump, dynamo, USB module, quick connector, and LED lights. Data were collected through expert validation conducted by Special School (SLB) teachers to assess the feasibility of the media and learning materials. The results showed that the demonstration tool met the feasibility criteria in terms of appearance, practicality, quality, and relevance to learning objectives. The media feasibility score reached an average of 95%, categorized as "very feasible," while the material feasibility scores also reached 95% in the same category. These findings indicate that the developed hydroelectric power plant demonstration tool is highly feasible and effective in supporting science learning for children with intellectual disabilities.